Deskripsi Tipologi, Klasifikasi dan Analisis Perancangan Masjid di Malaysia - Utaberta, Nangkula; Rasdi, Mohamad Tajuddin Mohamad (el Harakah: Jurnal Budaya Islam, 2010)
As one of the countries with the largest Moslem communities in Southeast Asia, the study of Islamic architecture, especially the architecture of  modern mosques in Malaysia, has not yet been done intensively. Most of the  studies and documentation carried out were more focused in the study of old  mosques which were considered as more valuable historically with a more unique  traditional architecture. This paper will attempt to describe the typology of form  and visual style of the mosques (as the main building of Islamic architecture)  developed in Malaysia, ranging from traditional mosques in the area of  remote villages to modern mosques in urban areas. This study is very  important in  recognizing aspects of morphology, the influence, and the development of mosque  design in Malaysia which will become a reference in designing the mosque,  especially in this country in the future. The discussion itself will consists of the Traditional Vernacular Mosque Architecture of Malaysia, a Sino Eclectic Mosques in Malaysia, the European Classical Mosque in Malaysia, the  North Indian Mosque in Malaysia, the Malaysia’s Vernacular Mo  dern Mosque, the Modern Expressionism Revivalism Mosque in Malaysia and the Post-Modern Mosque in Malaysia. It is expected that this  study would give an idea of the various approaches and the development  of mosque design in Malaysia in order to recognize the ideas and thoughts of Islamic architecture in Malaysia. Sebagai salah satu negara dengan komunitas muslim terbesar di Asia Tenggara, studi arsitektur Islam, terutama arsitektur masjid modern di Malaysia, belum dilakukan secara intensif. Sebagian besar studi dan dokumentasi yang dilakukan lebih difokuskan pada kajian masjid tua yang dianggap lebih bernilai historis dengan arsitektur tradisional yang lebih unik. Makalah ini menggambarkan tipologi bentuk dan gaya visual masjid (sebagai bangunan utama arsitektur Islam) yang dikembangkan di Malaysia, mulai dari masjid tradisional di daerah terpencil hingga masjid modern di daerah perkotaan. Studi ini sangat penting dalam mengenali aspek morfologi, pengaruh, dan perkembangan desain masjid di Malaysia yang akan menjadi acuan dalam merancang masjid, terutama di negeri ini di masa depan. Diskusi itu sendiri terdiri dari Arsitektur Masjid Tradisional Vernakular Malaysia, sebuah Masjid Ekaristi Sino di Malaysia, Masjid Klasik Eropa di Malaysia, Masjid India Utara di Malaysia, Masjid Vernacular Mo dern Malaysia, Masjid Modern Expressionism Revivalism di Malaysia dan Masjid Post-Modern di Malaysia. Diharapkan penelitian ini akan memberi gambaran tentang berbagai pendekatan dan pengembangan desain masjid di Malaysia untuk bisa mengenali gagasan dan pemikiran arsitektur Islam di Malaysia.